Examining the Efficacy of Calcium Hydroxylapatite Filler With Integral Lidocaine in Correcting Volume Loss of the Jawline-A Pilot Study - Juhász, Margit L W; Marmur, Ellen S (Dermatologic surgery, 2018)
Patients seek 3-dimensional volume restoration of the jawline to obtain a "defined" line. Injection of filler into the jawline is not approved by the Food and Drug Administration; however, dermatologists have injected this area with positive results, minimal adverse events, and high patient satisfaction. This study explores the efficacy of premixed calcium hydroxylapatite filler with integral lidocaine [CaHA(+)] to correct volume defects of the jawline. It examines the longevity, safety, and patient satisfaction (up to 12 months) of CaHA(+) for jawline volume loss correction. This is a single-investigator, nonblinded study. Twenty subjects received CaHA(+) filler injection in the jawline, with follow-up evaluations conducted at 14 days, 6 weeks, and 3, 6, 9, and 12 months. CaHA(+) injection in the jawline results in statistically significant restoration in volume and improvement in appearance lasting up to 12 months. Overall, subjects report "moderate" improvement on the Global Aesthetic Improvement Scale. It is important for cosmetic surgeons and dermatologists to have access to data on the efficacy and safety of injectables. The data obtained in this study show that CaHA(+) is an effective and safe option to correct jawline volume loss and is associated with high patient satisfaction.